Sulfatide Preserves Insulin Crystals Not by Being Integrated in the Lattice but by Stabilizing Their Surface - Karsten Buschard; Austin W. Bracey; Daniel L. McElroy; Andrew T. Magis; Thomas Osterbye; Mark A. Atkinson; Kate M. Bailey; Amanda L. Posgai; David A. Ostrov (Journal of Diabetes Research)
Background. Sulfatide is known to chaperone insulin crystallization within the pancreatic beta cell, but it is not known if this results from sulfatide being integrated inside the crystal structure or by binding the surface of the crystal. With this study, we aimed to characterize the molecular mechanisms underlying the integral role for sulfatide in stabilizing insulin crystals prior to exocytosis. Methods. We cocrystallized human insulin in the presence of sulfatide and solved the structure by molecular replacement. Results. The crystal structure of insulin crystallized in the presence of sulfatide does not reveal ordered occupancy representing sulfatide in the crystal lattice, suggesting that sulfatide does not permeate the crystal lattice but exerts its stabilizing effect by alternative interactions such as on the external surface of insulin crystals. Conclusions. Sulfatide is known to stabilize insulin crystals, and we demonstrate here that in beta cells sulfatide is likely coating insulin crystals. However, there is no evidence for sulfatide to be built into the crystal lattice.